Islam og demokrati - Paludan, Peter Steensgaard (Religionsvidenskabeligt Tidsskrift, 2004)
This study - "Islam and Democracy. A Critique of a Central Aspect of Samuel Huntington’s Theory about The Clash of Civilizations" - is testing Huntington’s argument that a decisive cause of the supposed clash of Western and Muslim culture in the period after the Cold War is the attempt to the West to export democracy and human rights to non-Western countries. Huntington sees the construction of socalled "Asian values" as a genuine expression of authentic "Asian" culture and the negative views in conservative of Islamist circles in the Muslim world of (some of) the international human rights as products of Western culture and therefore not valid in the Muslim world likewise as expressions of Muslim majority culture. The article points out that hte "Asian values" are a political construction that aims at rejecting critique from outside and inside of the violations by certain Muslim human righs schemes, the Universal Islamic Declaration of Human Rights and the Cairo Declaration, have to be understood as expressions of a conservative or Islamist interpretation of Islam. The quest for an international recognition of them as a genuine Islamic alternataive to the international human rights has the same purpose as the "Asian values". Next, the article examines the results of the World Value Survey in the Islamic workd. A major part of the Muslim populations has been surveyed. The results demonstrate that the average support of democracy - the democratic idea as well as the capability of democratic governance to solve democracy - is as high as it is in the West. The majority of the Muslim populations clearly want democracy in the own states. The main factor behind this openness towards democratic ideas seems to be raising levels of standards of living. Finally, the article points to the fact that the Islamist circles today seem to be somewhat weakened. But they are still the most well-organized political opposition group and therefore able to create problems in Middle East societies where liberalizations are initiated. Some Islamists, however, e.g. in Egypt and in particular in Turkey, have adapted democratic ideas. On this background the author rejects Huntington’s idea of a clash between the Islamic and Western world due to basic disagreement on human rights and democracy. Most modern Muslims apparently live with a Muslim piety combined with wishes for democracy in their own countries.